MENGEMBANGKAN KREATIVITAS ANAK MELALUI KEGIATAN TARI KREATIF YANG MENGGUNAKAN METODE BERMAIN DAN BERCERITA - Juniasih, Indah (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2012)
Children’s creativity should be developed as early as possible and the parents and teachers can use a number of methods to do. One of the methods is doing activities employing joyful learning method suitable for the children’s needs. This article discusses how creative dance can be practised to develop children’s creativity. Many parents and teachers think learning to dance for the pre-school aged children is just to practise their interest or hobby in arts exercising their motor skill. The article concludes that through interesting learning process and appropriate method, learning to dance can accommodate the needs of the pre-school aged children and is effective in developing their creativity. It is strongly recommended, the creative dance applying games and story telling methods is to be used as one of the effective activities for to develop the creativity of the pre-school aged children, as the mehtods do not only transfer movement and emphasize the learning achievement, but also transfer knowledge and emphasize creative process of learning